Religious Moderation Curriculum Reception Based On Qur’ani Principles - Eva Ardinal; Nurul Alamin; Luqyana Azmiya Putri; Ainil Khuryati; Oki Mitra (At Turots: Jurnal Pendidikan Islam, 2023)
Religious life in Indonesia has recently been under intense scrutiny both from within and outside the country. All of this is because social conflicts originating from religion continue to emerge. They start from cases of religious blasphemy, hate speech, suicide attacks, insults, destruction of places of worship, and terrorism. This paper offers a reception of a religious moderation curriculum based on Qur'anic principles. The research method used is qualitative research with a library research approach. The results of this study indicate that the reception of religious moderation curriculum can be formed from the exploration of verses of the Qur'an such as Tawassuth in surah Al-Baqarah verse 143, Tasamuh in surah Al-Mumtahanah verse 8, I'tidal contained in surah Al- Maidah verse 8, Tawazun in surah Al-Hadid verse 25, and Musawah in surah al-Hujurat verse 13. The results of the analysis and exploration of the verses of the Qur'an finally led to the creation of Basic Competency recommendations (KD) or Learning Achievement (CP). Sequentially the KD or CP consists of 1) building students' awareness so they don't easily blame others and always put forward a middle attitude; 2) application of respect for religious, ethnic, cultural, social, and community differences; 3) strengthening faith in the holy Qur'an and respecting the existence of other people's holy books 4) instilling the paradigm that general knowledge and religion are equally essential to learn; 5) raise awareness that there is no discrimination against opportunities for achievement and increase self-capacity.